Panacea, Curse, or Nonevent? : Unconventional Monetary Policy in the United Kingdom - Meier, Andre (IMF Working Papers; Working Paper ;, 2009)
The Bank of England's current "quantitative easing" strategy has given rise to a controversial debate about the effects and risks of unconventional monetary policy. The present paper makes two contributions to this debate. First, it provides a systematic overview of unconventional policy options, drawing from existing theoretical and empirical studies. Against this backdrop, it then analyzes the BoE's specific policies, discussing their effectiveness so far and putting them into a cross-country context. Tentative evidence on the BoE's quantitative easing is moderately encouraging, although the strategy is neither guaranteed to succeed nor as perilous as some of its detractors claim.